Comprehensive Review Of Healthcare Workforce Needs, Training, And Long-Term Workforce Planning (The Review of Diabetic Studies, 2024)
The healthcare workforce is the vital benchmark for rendering proper healthcare across the globe. More so, as populations age, chronic diseases grow, and the improvement and expansion of healthcare systems are advanced, there is a dire need for a skilled and sufficiently strong healthcare workforce. This review assesses the existing supply of the healthcare workforce, the general education course to join the healthcare profession, and the adequacy of long-term healthcare workforce planning. Depending on the gaps in manpower supply, training dearth, and upcoming demand, the paper provides solutions for fighting the healthcare workforce shortage. Technological improvement, policies and change, and new approaches to developing a sustainable and fair health workforce are also discussed.